2022
DOI: 10.3390/en15166094
|View full text |Cite
|
Sign up to set email alerts
|

Towards Data-Driven Models in the Prediction of Ship Performance (Speed—Power) in Actual Seas: A Comparative Study between Modern Approaches

Abstract: In the extremely competitive environment of shipping, minimizing shipping cost is the key factor for the survival and growth of shipping companies. However, stricter rules and regulations that aim at the reduction of greenhouse gas emissions published by the International Maritime Organization, force shipping companies to increase the operational efficiency of their fleet. The prediction of a ship speed in actual seas with a given power by its engine is the most important performance indicator and thus makes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The performance and emissions parameters of several engine types were predicted using linear regression [4] and SVR [5]. A review of data-driven models for ship performance was conducted by Alexiou et al [6]. Random forest regression was used to predict the combustion profile parameters in [7], whereas decision trees were proven effective for energy demand modelling [8].…”
Section: Introductionmentioning
confidence: 99%
“…The performance and emissions parameters of several engine types were predicted using linear regression [4] and SVR [5]. A review of data-driven models for ship performance was conducted by Alexiou et al [6]. Random forest regression was used to predict the combustion profile parameters in [7], whereas decision trees were proven effective for energy demand modelling [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mohamed et al suggested multiple machine learning models to predict eleven different parameters for proton exchange membrane (PEM) electrolyzer cells to achieve optimum design [9]. Recently, machine learning has shown great promise in computational fluid dynamics (CFD) studies [10] and is becoming more accurate and faster [11,12]. Making machine learning models with acceptable generalization capabilities for different heat transfer problems is another approach that has made analysis faster.…”
Section: Introductionmentioning
confidence: 99%